(untitled) (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2025)
This study aims to analyze the influence of Word of Mouth on Customer Interest in using products or services. Word of Mouth has emerged as one of the most effective promotional strategies due to its strong impact through personal experiences and recommendations. The research applies a quantitative approach using simple linear regression analysis. The population in this study consists of customers who have received product information through Word of Mouth, with purposive sampling techniques. Data were collected through questionnaires and analyzed using the latest version of SPSS software. The regression test results indicate that the Word of Mouth variable has a positive and significant effect on Customer Interest, as evidenced by a t-count of 8.284 > t-table of 1.677 and a significance value of 0.000 < 0.05. This suggests that the higher the intensity of Word of Mouth, the greater the customer’s interest in the offered product. The conclusion of this study shows that Word of Mouth is an effective strategy in influencing potential customers’ decisions. Therefore, businesses must manage word-of-mouth communication effectively by providing satisfying services, creating positive experiences, and involving customers as brand ambassadors. This research is expected to serve as a reference in designing marketing strategies based on relationships and consumer trust.